2019
DOI: 10.3390/app9153063
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Alzheimer’s Disease on the Basis of a Voxel-Wise Approach

Abstract: Robust prediction of Alzheimer's disease (AD) helps in the early diagnosis of AD and may support the treatment of AD patients. In this study, for early detection of AD and prediction of mild cognitive impairment (MCI) conversion, we develop an automatic computer-aided diagnosis (CAD) framework based on a merit-based feature selection method through a whole-brain voxel-wise analysis using baseline magnetic resonance imaging (MRI) data. We also explore the impact of different MRI spatial resolution on the voxel-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…However, these types of models have been found to be unsuitable for the evaluation of narrow age ranges, such as the younger or elderly groups. Several studies have reported the bias estimation of different age range groups, underestimation of younger ages, and overestimation of older age due to the systematic bias of inherent regression methods [11,42]. In fact, our model also demonstrated an inherent bias in brain age prediction in elderly brains (Fig.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…However, these types of models have been found to be unsuitable for the evaluation of narrow age ranges, such as the younger or elderly groups. Several studies have reported the bias estimation of different age range groups, underestimation of younger ages, and overestimation of older age due to the systematic bias of inherent regression methods [11,42]. In fact, our model also demonstrated an inherent bias in brain age prediction in elderly brains (Fig.…”
Section: Discussionmentioning
confidence: 57%
“…Brain age represents not only the current brain aging status but also the acceleration of brain aging [7,8] by using the difference between chronological age and predicted age [9]. These differences have been associated with a number of neurodevelopmental [10] and neurodegenerative diseases, such as Alzheimer's disease (AD) and Parkinson's disease [11].…”
Section: Introductionmentioning
confidence: 99%
“…Early diagnosis of AD produced promising outcomes. Furthermore, to find out the stable MCI (sMCI) and progressive MCI (pMCI) is a challenging task for researchers (Beheshti et al, 2019). The ADNI healthcare database consists of data on every individual's enlistment, demography, physical exams, and critical concentration.…”
Section: Introductionmentioning
confidence: 99%